The Caja Nacional de Ahorros and State-Owned Banks: A Successful Case of Associative Economy Among Financial Banks in Chile, C. 1920-1950 - Gonzalez-Correa, I (EDIT UM-EDICIONES UNIV MURCIA, 2021)
This work examines the links among the Caja Nacional de Ahorros (National Savings Bank) and other state-owned banks such as the Caja de Credito Hipotecario (National Mortgage Bank) and the Caja de Credito Agrario (Agricultural Credit Bank) from the end of the nineteenth-century to the first half of the twentieth-century. The permanent financial links, the operative cooperation, and the shared Board of Directors among the "cajas" explain the success and permanence in the market of the three state-owned firms. In addition, this work shows the relevance of the Caja Nacional de Ahorros in the Chilean savings market: in 1922 more than 50 percent of the people in Santiago and more than 25 percent of the country s population had a savings account of the National Savings Bank , that is, practically all the families in the country had a savings account in this institution. The wide presence of offices of the Caja Nacional de Ahorros in cities and towns where no private bank had branches and its system of field visits allowed it to capture many customers, especially the working class, who were willing to save in the formal financial system. Finally, the history of close relationships among these companies is one of the main factors that explain why these institutions were merged in 1953 to form the Banco del Estado de Chile.